Management of alien fishes in the Murray‐Darling Basin. (March 2014) - Barrett, Jim; Bamford, Heleena; Jackson, Peter
Summary: Native Fish Strategy 2003–2013 (NFS) investment over the past decade has considerably improved alien fish management for the Murray‐Darling Basin. The NFS delivered a wide and varied portfolio of activities on alien fish management – planning, social aspects, on‐ground management and a major investment in research. Control of Carp ( Cyprinus carpio ) was a key feature; however approaches moved beyond this one species to address multiple species and to take a more holistic approach, advocating integrated pest management and linking alien fish with native fish management and broader river rehabilitation. The NFS provided leadership for the management of alien fish in the Basin and established a framework to guide future efforts in this field through the development of a draft Basin Alien Fish Plan.